THE RETURN OF INDONESIAN CULTURAL PROPERTYTHROUGH INTERNATIONAL LAW AND NATIONAL LAWREFORM - Nuraini (2021)
A number of Indonesian cultural properties are stolen and illegally exported, makes Indonesia has to determine its effort to return these cultural properties to Indonesia. The absence of ratified international agreements and bilateral agreements to return the cultural property as regulated in Article 20 of Law Nr. 11 of 2010 concerning Cultural Conservation makes Indonesia still depends on diplomacy between countries. This article analyzes the advantages of ratifying the 1970 UNESCO Convention and the 1995 UNIDROIT Convention to reform Law Nr. 11 of 2010 therefore it can protect the cultural property in a better and comprehensive way, also to analyzes the concept of regulation regarding returning of the cultural property based on other countries' regulation and international cooperation. This study aims to determine the urgency of Indonesia to ratify the 1970 Convention and the 1995 Convention also to reform the regulation of the return of cultural property in Law Nr. 11 of 2010.